Secure and trustworthy cyberphysical microfluidic biochips : a practical guide to cutting-edge design techniques for implementing secure and trustworthy cyberphysical microfluidic biochips /: a practical guide to cutting-edge design techniques for implementing secure and trustworthy cyberphysical microfluidic biochips. ([2020]) - Tang, Jack; Ibrahim, Mohamed; Chakrabarty, Krishnendu; Karri, Ramesh
No abstract available